Recent advances in Cu-catalyzed C(sp3)–Si and C(sp3)–B bond formation - Takale, Balaram S.; Thakore, Ruchita R.; Etemadi-Davan, Elham; Lipshutz, Bruce H. (Beilstein Journal of Organic Chemistry, 2020)
Numerous reactions generating C–Si and C–B bonds are in focus owing to the importance of incorporating silicon or boron into new or existing drugs, in addition to their use as building blocks in cross-coupling reactions en route to various targets of both natural and unnatural origins. In this review, recent protocols relying on copper-catalyzed sp3 carbon–silicon and carbon–boron bond-forming reactions are discussed.
Keywords: C–B bonds; copper catalysis; C–Si bonds; enantioselective reactions; sp3 carbon functionalization

(untitled) - Cheng, C.; Hartwig, J. F. (Chem. Rev., 2015)

(untitled) - Hatanaka, Y.; Hiyama, T. (J. Org. Chem., 1988)

(untitled) - Denmark, S. E.; Regens, C. S. (Acc. Chem. Res., 2008)

(untitled) - Miyaura, N.; Suzuki, A. (Chem. Rev., 1995)

(untitled) - Jacob, P., III; Brown, H. C. (J. Org. Chem., 1977)

(untitled) - Essafi, S.; Tomasi, S.; Aggarwal, V. K.; Harvey, J. N. (J. Org. Chem., 2014)

(untitled) - Brown, H. C.; Rogic, M. M.; Nambu, H.; Rathke, M. W. (J. Am. Chem. Soc., 1969)

(untitled) - Franz, A. K.; Wilson, S. O. (J. Med. Chem., 2013)

(untitled) - Mortensen, M.; Husmann, R.; Veri, E.; Bolm, C. (Chem. Soc. Rev., 2009)

(untitled) - Fujii, S.; Hashimoto, Y. (Future Med. Chem., 2017)

(untitled) - Geyer, M.; Wellner, E.; Jurva, U.; Saloman, S.; Armstrong, D.; Tacke, R. (ChemMedChem, 2015)

(untitled) - Singh, S.; Sieburth, S. M. (Org. Lett., 2012)

(untitled) - Baker, S. J.; Tomsho, J. W.; Benkovic, S. J. (Chem. Soc. Rev., 2011)

(untitled) - Diaz, D. B.; Yudin, A. K. (Nat. Chem., 2017)

(untitled) - Baker, S. J.; Ding, C. Z.; Akama, T.; Zhang, Y.-K.; Hernandez, V.; Xia, Y. (Future Med. Chem., 2009)

(untitled) - Groziak, M. P. (Am. J. Ther., 2001)

(untitled) - Bähr, S.; Xue, W.; Oestreich, M. (ACS Catal., 2019)

(untitled) - Keipour, H.; Carreras, V.; Ollevier, T. (Org. Biomol. Chem., 2017)

(untitled) - Wilkinson, J. R.; Nuyen, C. E.; Carpenter, T. S.; Harruff, S. R.; Van Hoveln, R. (ACS Catal., 2019)

Progress in Enantioselective Cu(I)-catalyzed Formation of Stereogenic Centers - Hensel, A.; Oestreich, M. (Asymmetric Addition of Boron and Silicon Nucleophiles, 2015)

(untitled) - Hemming, D.; Fritzemeier, R.; Westcott, S. A.; Santos, W. L.; Steel, P. G. (Chem. Soc. Rev., 2018)

(untitled) - Neeve, E. C.; Geier, S. J.; Mkhalid, I. A. I.; Westcott, S. A.; Marder, T. B. (Chem. Rev., 2016)

(untitled) - Mkhalid, I. A. I.; Barnard, J. H.; Marder, T. B.; Murphy, J. M.; Hartwig, J. F. (Chem. Rev., 2010)

(untitled) - Collins, B. S. L.; Wilson, C. M.; Myers, E. L.; Aggarwal, V. K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Okuda, Y.; Morizawa, Y.; Oshima, K.; Nozaki, H. (Tetrahedron Lett., 1984)

(untitled) - Takeda, M.; Shintani, R.; Hayashi, T. (J. Org. Chem., 2013)

(untitled) - Scharfbier, J.; Oestreich, M. (Synlett, 2016)

(untitled) - Scharfbier, J.; Hazrati, H.; Irran, E.; Oestreich, M. (Org. Lett., 2017)

(untitled) - Xue, W.; Qu, Z.-W.; Grimme, S.; Oestreich, M. (J. Am. Chem. Soc., 2016)

(untitled) - Guisán-Ceinos, M.; Soler-Yanes, R.; Collado-Sanz, D.; Phapale, V. B.; Buñuel, E.; Cárdenas, D. J. (Chem. – Eur. J., 2013)

(untitled) - Xue, W.; Oestreich, M. (Angew. Chem., Int. Ed., 2017)

(untitled) - Hazrati, H.; Oestreich, M. (Org. Lett., 2018)

(untitled) - Sun, H.; Moeller, K. D. (Org. Lett., 2002)

(untitled) - Min, G. K.; Hernández, D.; Skrydstrup, T. (Acc. Chem. Res., 2013)

(untitled) - Suginome, M.; Matsuda, T.; Ito, Y. (Organometallics, 2000)

(untitled) - Vyas, D. J.; Fröhlich, R.; Oestreich, M. (Org. Lett., 2011)

(untitled) - Park, J. K.; Lackey, H. H.; Ondrusek, B. A.; McQuade, D. T. (J. Am. Chem. Soc., 2011)

(untitled) - Hensel, A.; Nagura, K.; Delvos, L. B.; Oestreich, M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Mita, T.; Sugawara, M.; Saito, K.; Sato, Y. (Org. Lett., 2014)

(untitled) - Zhao, C.; Jiang, C.; Wang, J.; Wu, C.; Zhang, Q.-W.; He, W. (Asian J. Org. Chem., 2014)

(untitled) - Chen, Z.; Huo, Y.; An, P.; Wang, X.; Song, C.; Ma, Y. (Org. Chem. Front., 2016)

(untitled) - Kleeberg, C.; Feldmann, E.; Hartmann, E.; Vyas, D. J.; Oestreich, M. (Chem. – Eur. J., 2011)

(untitled) - Takeda, M.; Yabushita, K.; Yasuda, S.; Ohmiya, H. (Chem. Commun., 2018)

(untitled) - Takeda, M.; Mitsui, A.; Nagao, K.; Ohmiya, H. (J. Am. Chem. Soc., 2019)

(untitled) - Cirriez, V.; Rasson, C.; Hermant, T.; Petrignet, J.; Díaz Álvarez, J.; Robeyns, K.; Riant, O. (Angew. Chem., Int. Ed., 2013)

(untitled) - Delvos, L. B.; Hensel, A.; Oestreich, M. (Synthesis, 2014)

Organometallics in Synthesis: A Manual - Lipshutz, B. H. (Organocopper Chemistry, 2002)

(untitled) - Hartmann, E.; Vyas, D. J.; Oestreich, M. (Chem. Commun., 2011)

(untitled) - Ager, D. J.; Fleming, I. (J. Chem. Soc., Chem. Commun., 1978)

(untitled) - Ager, D. J.; Fleming, I.; Patel, S. K. (J. Chem. Soc., Perkin Trans. 1, 1981)

(untitled) - Fleming, I.; Newton, T. W. (J. Chem. Soc., Perkin Trans. 1, 1984)

(untitled) - Lipshutz, B. H.; Reuter, D. C.; Ellsworth, E. L. (J. Org. Chem., 1989)

(untitled) - Lipshutz, B. H.; Sclafani, J. A.; Takanami, T. (J. Am. Chem. Soc., 1998)

(untitled) - Ito, H.; Ishizuka, T.; Tateiwa, J.-i.; Sonoda, M.; Hosomi, A. (J. Am. Chem. Soc., 1998)

(untitled) - Iannazzo, L.; Molander, G. A. (Eur. J. Org. Chem., 2012)

(untitled) - Auer, G.; Weiner, B.; Oestreich, M. (Synthesis, 2006)

(untitled) - Lee, K.-s.; Hoveyda, A. H. (J. Am. Chem. Soc., 2010)

(untitled) - Lee, K.-s.; Wu, H.; Haeffner, F.; Hoveyda, A. H. (Organometallics, 2012)

(untitled) - Pace, V.; Rae, J. P.; Harb, H. Y.; Procter, D. J. (Chem. Commun., 2013)

(untitled) - Pace, V.; Rae, J. P.; Procter, D. J. (Org. Lett., 2014)

(untitled) - Miyamoto, S.; Mori, A. (Neuroscience, 1985)

(untitled) - Zhang, L.; Liu, D.; Liu, Z.-Q. (Org. Lett., 2015)

(untitled) - Lan, Y.; Chang, X.-H.; Fan, P.; Shan, C.-C.; Liu, Z.-B.; Loh, T.-P.; Xu, Y.-H. (ACS Catal., 2017)

(untitled) - Plotzitzka, J.; Kleeberg, C. (Organometallics, 2014)

(untitled) - López, A.; Parra, A.; Jarava-Barrera, C.; Tortosa, M. (Chem. Commun., 2015)

(untitled) - Da, B.-C.; Liang, Q.-J.; Luo, Y.-C.; Ahmad, T.; Xu, Y.-H.; Loh, T.-P. (ACS Catal., 2018)

(untitled) - Ahmad, T.; Li, Q.; Qiu, S.-Q.; Xu, J.-L.; Xu, Y.-H.; Loh, T.-P. (Org. Biomol. Chem., 2019)

(untitled) - Mao, W.; Xue, W.; Irran, E.; Oestreich, M. (Angew. Chem., Int. Ed., 2019)

(untitled) - Shen, J.-J.; Gao, Q.; Wang, G.; Tong, M.; Chen, L.; Xu, S. (ChemistrySelect, 2019)

(untitled) - Zhang, Y.; Tong, M.; Gao, Q.; Zhang, P.; Xu, S. (Tetrahedron Lett., 2019)

(untitled) - Lipshutz, B. H. (Curr. Opin. Green Sustainable Chem., 2018)

(untitled) - Lipshutz, B. H.; Gallou, F.; Handa, S. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Lipshutz, B. H.; Ghorai, S. (Green Chem., 2014)

(untitled) - Kitanosono, T.; Zhu, L.; Liu, C.; Xu, P.; Kobayashi, S. (J. Am. Chem. Soc., 2015)

(untitled) - Tani, Y.; Fujihara, T.; Terao, J.; Tsuji, Y. (J. Am. Chem. Soc., 2014)

(untitled) - Zhang, Y.-Z.; Zhu, S.-F.; Wang, L.-X.; Zhou, Q.-L. (Angew. Chem., Int. Ed., 2008)

(untitled) - Keipour, H.; Jalba, A.; Delage-Laurin, L.; Ollevier, T. (J. Org. Chem., 2017)

WO Patent - Brandstadt, K.; Cook, S.; Nguyen, B. T.; Surgenor, A.; Taylor, R.; Tzou, M.-S. (Copper Containing Hydrosilylation Catalysts and Compositions Containing the Catalysts, 2013)

(untitled) - Gribble, M. W., Jr; Pirnot, M. T.; Bandar, J. S.; Liu, R. Y.; Buchwald, S. L. (J. Am. Chem. Soc., 2017)

(untitled) - Shi, Y.; Gao, Q.; Xu, S. (J. Org. Chem., 2018)

(untitled) - Feng, J.-J.; Oestreich, M. (Org. Lett., 2018)

(untitled) - Feng, J.-J.; Oestreich, M. (Angew. Chem., Int. Ed., 2019)

(untitled) - Yi, H.; Oestreich, M. (Chem. – Eur. J., 2019)

(untitled) - Takeda, Y.; Shibuta, K.; Aoki, S.; Tohnai, N.; Minakata, S. (Chem. Sci., 2019)

(untitled) - Zhang, L.; Oestreich, M. (Chem. – Eur. J., 2019)

(untitled) - Meng, F.-F.; Xie, J.-H.; Xu, Y.-H.; Loh, T.-P. (ACS Catal., 2018)

(untitled) - Lee, K.-s.; Zhugralin, A. R.; Hoveyda, A. H. (J. Am. Chem. Soc., 2009)

(untitled) - Ramírez, J.; Sanaú, M.; Fernández, E. (Angew. Chem., Int. Ed., 2008)

(untitled) - Guo, W.-H.; Zhao, H.-Y.; Luo, Z.-J.; Zhang, S.; Zhang, X. (ACS Catal., 2019)

(untitled) - Lawson, Y. G.; Gerald Lesley, M. J.; Norman, N. C.; Rice, C. R.; Lawson, Y. G.; Marder, T. B. (Chem. Commun., 1997)

(untitled) - Yang, L.; Uemura, N.; Nakao, Y. (J. Am. Chem. Soc., 2019)

(untitled) - Hemming, D.; Fritzemeier, R.; Westcott, S. A.; Santos, W. L.; Steel, P. G. (Chem. Soc. Rev., 2018)

(untitled) - Ito, H.; Kawakami, C.; Sawamura, M. (J. Am. Chem. Soc., 2005)

(untitled) - Guzman-Martinez, A.; Hoveyda, A. H. (J. Am. Chem. Soc., 2010)

(untitled) - Yamamoto, E.; Takenouchi, Y.; Ozaki, T.; Miya, T.; Ito, H. (J. Am. Chem. Soc., 2014)

(untitled) - Zhong, C.; Kunii, S.; Kosaka, Y.; Sawamura, M.; Ito, H. (J. Am. Chem. Soc., 2010)

(untitled) - Kojima, R.; Akiyama, S.; Ito, H. (Angew. Chem., Int. Ed., 2018)

(untitled) - Dang, L.; Zhao, H.; Lin, Z.; Marder, T. B. (Organometallics, 2007)

(untitled) - Xi, Y.; Hartwig, J. F. (J. Am. Chem. Soc., 2016)

(untitled) - Xi, Y.; Hartwig, J. F. (J. Am. Chem. Soc., 2017)

(untitled) - Guisán-Ceinos, M.; Parra, A.; Martín-Heras, V.; Tortosa, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Jarava-Barrera, C.; Parra, A.; López, A.; Cruz-Acosta, F.; Collado-Sanz, D.; Cárdenas, D. J.; Tortosa, M. (ACS Catal., 2016)

(untitled) - Su, W.; Gong, T.-J.; Lu, X.; Xu, M.-Y.; Yu, C.-G.; Xu, Z.-Y.; Yu, H.-Z.; Xiao, B.; Fu, Y. (Angew. Chem., Int. Ed., 2015)

(untitled) - Jia, T.; Cao, P.; Wang, B.; Lou, Y.; Yin, X.; Wang, M.; Liao, J. (J. Am. Chem. Soc., 2015)

(untitled) - Jiang, L.; Cao, P.; Wang, M.; Chen, B.; Wang, B.; Liao, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Chen, B.; Cao, P.; Liao, Y.; Wang, M.; Liao, J. (Org. Lett., 2018)

(untitled) - Yang, Y. (Angew. Chem., Int. Ed., 2016)

(untitled) - Wu, N.-Y.; Xu, X.-H.; Qing, F.-L. (ACS Catal., 2019)

(untitled) - Gan, X.-C.; Zhang, Q.; Jia, X.-S.; Yin, L. (Org. Lett., 2018)

(untitled) - Li, X.; Meng, F.; Torker, S.; Shi, Y.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2016)

(untitled) - Jia, T.; He, Q.; Ruscoe, R. E.; Pulis, A. P.; Procter, D. J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zhao, W.; Montgomery, J. (J. Am. Chem. Soc., 2016)

(untitled) - Zhao, W.; Montgomery, J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kim, H. K.; Mane, M. V.; Montgomery, J.; Baik, M.-H. (Chem. – Eur. J., 2019)

(untitled) - Bergmann, A. M.; Dorn, S. K.; Smith, K. B.; Logan, K. M.; Brown, M. K. (Angew. Chem., Int. Ed., 2019)

(untitled) - Semba, K.; Ohtagaki, Y.; Nakao, Y. (Org. Lett., 2016)

(untitled) - Logan, K. M.; Smith, K. B.; Brown, M. K. (Angew. Chem., Int. Ed., 2015)

(untitled) - Logan, K. M.; Brown, M. K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Huang, Y.; Smith, K. B.; Brown, M. K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Smith, K. B.; Huang, Y.; Brown, M. K. (Angew. Chem., Int. Ed., 2018)

(untitled) - Yang, Y.; Perry, I. B.; Buchwald, S. L. (J. Am. Chem. Soc., 2016)

(untitled) - Smith, J. J.; Best, D.; Lam, H. W. (Chem. Commun., 2016)

(untitled) - Itoh, T.; Kanzaki, Y.; Shimizu, Y.; Kanai, M. (Angew. Chem., Int. Ed., 2018)

(untitled) - Sakae, R.; Hirano, K.; Satoh, T.; Miura, M. (Angew. Chem., 2015)

(untitled) - Iwadate, N.; Suginome, M. (J. Am. Chem. Soc., 2010)

(untitled) - Sakae, R.; Hirano, K.; Miura, M. (J. Am. Chem. Soc., 2015)

(untitled) - Butcher, T. W.; McClain, E. J.; Hamilton, T. G.; Perrone, T. M.; Kroner, K. M.; Donohoe, G. C.; Akhmedov, N. G.; Petersen, J. L.; Popp, B. V. (Org. Lett., 2016)

(untitled) - Ito, H.; Yamanaka, H.; Tateiwa, J.-i.; Hosomi, A. (Tetrahedron Lett., 2000)

(untitled) - Ding, W.; Song, Q. (Org. Chem. Front., 2016)

(untitled) - Sole, C.; Fernández, E. (Chem. – Asian J., 2009)

(untitled) - Molander, G. A.; McKee, S. A. (Org. Lett., 2011)

(untitled) - Molander, G. A.; Wisniewski, S. R.; Hosseini-Sarvari, M. (Adv. Synth. Catal., 2013)

(untitled) - Lauberteaux, J.; Crévisy, C.; Baslé, O.; de Figueiredo, R. M.; Mauduit, M.; Campagne, J.-M. (Org. Lett., 2019)

(untitled) - Laitar, D. S.; Tsui, E. Y.; Sadighi, J. P. (J. Am. Chem. Soc., 2006)

(untitled) - Kubota, K.; Yamamoto, E.; Ito, H. (J. Am. Chem. Soc., 2015)

(untitled) - Kubota, K.; Osaki, S.; Jin, M.; Ito, H. (Angew. Chem., Int. Ed., 2017)

(untitled) - McIntosh, M. L.; Moore, C. M.; Clark, T. B. (Org. Lett., 2010)

(untitled) - Ishiyama, T.; Murata, M.; Miyaura, N. (J. Org. Chem., 1995)

(untitled) - Yang, C.-T.; Zhang, Z.-Q.; Tajuddin, H.; Wu, C.-C.; Liang, J.; Liu, J.-H.; Fu, Y.; Czyzewska, M.; Steel, P. G.; Marder, T. B.; Liu, L. (Angew. Chem., Int. Ed., 2012)

(untitled) - Akiyama, S.; Kubota, K.; Mikus, M. S.; Paioti, P. H. S.; Romiti, F.; Liu, Q.; Zhou, Y.; Hoveyda, A. H.; Ito, H. (Angew. Chem., Int. Ed., 2019)

(untitled) - Ito, H.; Kubota, K. (Org. Lett., 2012)

(untitled) - Bose, S. K.; Brand, S.; Omoregie, H. O.; Haehnel, M.; Maier, J.; Bringmann, G.; Marder, T. B. (ACS Catal., 2016)

(untitled) - Iwamoto, H.; Endo, K.; Ozawa, Y.; Watanabe, Y.; Kubota, K.; Imamoto, T.; Ito, H. (Angew. Chem., Int. Ed., 2019)

(untitled) - Wang, J.; Shang, M.; Lundberg, H.; Feu, K. S.; Hecker, S. J.; Qin, T.; Blackmond, D. G.; Baran, P. S. (ACS Catal., 2018)

(untitled) - Mao, L.; Szabó, K. J.; Marder, T. B. (Org. Lett., 2017)